Specific dynamic facial expression evoked responses show distinct perceptual and attentional features in autism connected to social communication and GABA phenotypes - Daniela Sousa; Ana Ferreira; Helena Catarina Pereira; Joana Amaral; Joana Crisóstomo; Marco Simões; Ricardo Martins; Susana Mouga; Frederico Duque; Guiomar Oliveira; Miguel Castelo-Branco (Scientific Reports)
Abstract Autism is characterised by core differences in social communication and interaction. The neurobiology underlying autism can be investigated using experimental designs that capture the dynamic nature of social perception, which activates the third visual pathway. Here, we investigated dynamic specific facial emotion processing using a naturalistic facial expression paradigm, leading to a specific dynamic N170 (dN170) evoked by emotion expression trajectories. Participants engaged in an active task of an avatar with two temporal trajectories: morphing from neutral to happy or sad expressions and unmorphing back to neutral. We recorded event-related potentials (ERPs) and magnetic resonance spectroscopy in autistic and non-autistic children and adolescents (n = 16 per group; ages between 8 and 17) matched for sex, handedness, and age. Results revealed that dN170 exhibited longer latencies during unmorphing for the autistic group. This specific timing effect, identified for the unmorphing versus morphing conditions in autism, suggests a stimulus trajectory-dependent effect (hysteresis). Dynamic P300 showed higher amplitudes in the autistic group during morphing, confirming the presence of an attentional compensatory mechanism. Correlations between ERP properties, GABA, and social communication abilities provided evidence of a dimensional continuum from non-autistic to autistic traits. These findings highlight the promising role of these ERPs as indicators of perceptual and attentional processing differences in autism.